(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This study has been undertaken as an attempt to examine the use of different super plasticizer dosage (0.5, 0.7, 0.9, 1.1 and 1.2) percentage of the weight of cement on the performance of the concrete and estimate the best ratio of super plasticizer. The laboratory experiments for both plastic and hardened properties of concrete for concrete mix grade 25 were determined and the effects were contrasted against normal concrete mixture. The tests performed for this study are slump test and compressive strength test .The findings demonstrate that with the raise of superplasticizer dose in concrete will lead to an improvement in the properties of concrete. The experimental calculations display a significant increase in the rate of compressive strength in comparison with the normal mix. The compressive strength increased about (47.43) % in comparison with the normal mix. Also, the experimental results showed the optimum ratio of the superplasticizer is (0.7)% of the weight of cement.